1995
DOI: 10.1159/000188512
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Interstitial Nephritis without Basement Membrane Changes

Abstract: Hereditary interstitial nephritides are a heterogeneous group of disorders comprising medullary cystic disease, several varieties of Alport’s syndrome and also one familial disorder with a distinct clinical syndrome and without characteristic ultrastructural glomerular basement membrane changes. Our family consisted of 11 members, 5 of which presented with renal dysfunction of varying degrees. Clinically, the affected siblings presented with long-standing hypertension, minimal proteinuria and no hematuria. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
6
2
Order By: Relevance
“…In other cases, a diagnosis of unspeci®ed familial interstitial nephritis could be possible, mainly if cysts are not found on imaging or biopsy [Coles et al, 1976;Richmond et al, 1981;Levy et al, 1995]. In our families, no medullary cysts have been identi®ed even at late stages of renal disease, contrary to previous descriptions [Garel et al, 1984].…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…In other cases, a diagnosis of unspeci®ed familial interstitial nephritis could be possible, mainly if cysts are not found on imaging or biopsy [Coles et al, 1976;Richmond et al, 1981;Levy et al, 1995]. In our families, no medullary cysts have been identi®ed even at late stages of renal disease, contrary to previous descriptions [Garel et al, 1984].…”
Section: Discussioncontrasting
confidence: 66%
“…Most of the cases of hereditary non-cystic nephropathy are associated with Alport syndrome [Barker et al, 1990]. However, other cases of hereditary nephritis exist which do not share any clinical similarities with Alport syndrome [Levy et al, 1995]. These cases, mostly of autosomal dominant inheritance, are mainly represented by medullary cystic kidney disease (ADMCKD) [Goldman et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these early reports, the disease remained a difficult diagnosis to make and some later reports propagated the confusion and uncertainty. To a large extent this was due to the variable phenotype which suggested that the MCD/FJN complex represented a heterogeneous group of disorders with similar functional and morphologic renal alterations [Goldman et al, 1966;Gardner, 1971;Wrigley et al, 1973;Swenson et al, 1974;Giangiacomo et al, 1975;Chamberlin et al, 1977;Bernstein and Gardner, 1983;Kleinknecht, 1990 and references therein; Levy et al, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Oda et al 14 reported the possible participation of the Cw1 locus in autosomal dominant nephronophthisis-medullary cystic disease complex. Similarly, Levy et al 15 reported an HLA association between affected and unaffected members with familial interstitial nephritis. They suggested a link between the disorder and HLA DQW7, which is located on chromosome 6.…”
Section: Discussionmentioning
confidence: 88%